Rivalitas Amerika Serikat-Tiongkok di Laut China Selatan dan Pengaruhnya Terhadap Indonesia - Dwiguna, Adrianus Revi; Rofii, Muhammad Syaroni (Jurnal Kajian Stratejik Ketahanan Nasional, 2019)
Dispute in the South China Sea (SCS) is one of the important issues in the last five years. The unilateral claim made by China caused a strong reaction from ASEAN countries, including Indonesia. The rejection of ASEAN countries against China's claim is based on the UNCLOS international law of the sea. Amid efforts to resolve territorial disputes in the SCS, recently the United States has emerged as a third party trying to reduce tensions in the SCS. However, the US move received a cold response from China. The US presence has actually made China show its military presence in the SCS through troop titles and construction of military installations. Such a situation in the LCS has the potential to create a military conflict involving two major powers. If a military confrontation takes place, it is certain that ASEAN countries will be directly involved in order to protect their national sovereignty. This research is a qualitative study that seeks to explain the root causes of territorial disputes in the SCS followed by US-China rivalries and their impact on Indonesia.